ANALISIS RASIO KEUANGAN APBD UNTUK MENILAI KINERJA KEUANGAN PEMERINTAH PROVINSI JAWA BARAT TAHUN ANGARAN 2020-2024 - Naning Setiani; Aris Eddy Sarwono (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2025)
This study aims to analyze the financial performance of the West Java Provincial Government using financial ratio analysis based on the Regional Budget (APBD) for the fiscal years 2020–2024. The research employs a descriptive quantitative method using secondary data from the Budget Realization Report. The analysis includes five financial ratios: fiscal independence, degree of fiscal decentralization, PAD effectiveness, expenditure harmony, and the share and growth of locally generated revenue (PAD). The results show that West Java’s financial performance is categorized as moderately good, with an increasing level of fiscal independence, although PAD effectiveness remains suboptimal. The fiscal capacity mapping places the province in quadrant II, indicating high PAD growth but a contribution level that still requires improvement. These findings reflect strong fiscal potential that needs more focused management strategies.